2016
DOI: 10.1590/1809-9823.2016.14210
|View full text |Cite
|
Sign up to set email alerts
|

Depressive disorders and comorbidities among the elderly: a population-based study

Abstract: Objective: The present study assessed the prevalence of depressive disorders and associated factors in a sample of elderly persons in the south of Santa Catarina. Methods: A crosssectional study based on population data was performed, evaluating 1021 elderly individuals aged between 60 and 79 years. Home interviews were carried out using the Portuguese version of the Mini International Neuropsychiatric Interview (MINI), in order to collect demographic data, information on hypertension and reports of acute myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…Recibido: 29 de septiembre 2021 Aceptado: 20 de febrero 2022 DOI: https://doi.org/10.47307/GMC.2022.130. 1.15 ORCID: 0000-0003-4553-4877 1 ORCID: 0000-0003-0515-4108 2 ORCID: 0000-0001-8737-0319 3 ORCID: 0000-0003-2252-2435 4 ORCID: 0000-0001-8232-0339 5 1 Nurse specialized in psychiatry and mental health. Universidade Nove de Julho (UNINOVE)-Rua Vergueiro, 235/249 -Liberdade, 01525-000 São Paulo, SP-Brasil.…”
Section: Resultados: La Depresión Y Las Ecv En Los Ancianos Es Un Pro...unclassified
“…Recibido: 29 de septiembre 2021 Aceptado: 20 de febrero 2022 DOI: https://doi.org/10.47307/GMC.2022.130. 1.15 ORCID: 0000-0003-4553-4877 1 ORCID: 0000-0003-0515-4108 2 ORCID: 0000-0001-8737-0319 3 ORCID: 0000-0003-2252-2435 4 ORCID: 0000-0001-8232-0339 5 1 Nurse specialized in psychiatry and mental health. Universidade Nove de Julho (UNINOVE)-Rua Vergueiro, 235/249 -Liberdade, 01525-000 São Paulo, SP-Brasil.…”
Section: Resultados: La Depresión Y Las Ecv En Los Ancianos Es Un Pro...unclassified
“…Estudo refere que a depressão configura-se como objeto complexo, de difícil observação e mensuração. Pois as queixas decorrentes da presença de doenças crônicas somáticas são mais exacerbadas, tornando os sintomas depressivos menos aparentes, o que pode prejudicar seu diagnóstico 10 .…”
Section: Discussionunclassified
“…In this sense, some authors have reported that women face widowhood differently from men, being less likely to seek a new relation, which can be a contributing factor to depressive disorders; in contrast, men usually remarry (19) . It can be inferred that even individuals who have never had a partner are more vulnerable to depression and consequent decreased QoL, noting that older women are more prone to depression (23) .…”
Section: Discussionmentioning
confidence: 99%